Teacher education intersecting comparative and international education revisiting research, policy and practice in twin scholarship fields - Salajan, Florin; Jules, Tavis Deryck 1980-; Wolhuter, Charl (Bloomsbury Academic, 2023)
"This book draws critical connections between teacher education or preparation and the field of comparative and international education (CIE) showing ways in which the two fields can inform and advance one another. The chapters consider how teacher education shapes and is shaped by CIE, particularly in an era of socio-cultural upheavals, politico-economic transformations and climate or health crises affecting the human and natural world. The question at the core of the book is: in what ways can comparative and international education support a rethinking of teacher education in the wake of the social movements for equity, justice and civil liberties with ramifications for educators around the world? It includes contributions from leading academics based in Argentina, Canada, China, Columbia, Finland, Grenada, Hong Kong, Myanmar, Spain, South Africa, Turkey and the USA. The chapters cover topics ranging from equity, social justice, and the sustainable development goals to country case-studies including teacher education in Myanmar and a comparative study of teacher preparation in South Korea and the USA."
Keywords: Teachers / Training of; Comparative education; International education; Educational strategies & policy; Teacher training